MiR-27a-3p exacerbates cell migration and invasion in right-sided/left-sided colorectal cancer by targeting TGFBR2/TCF7L2: MiR-27a-3p role in colorectal cancer - Bi, Lei; Zhou, Yuntao; Zhang, Yong; Zhang, Xin (Cellular and Molecular Biology, 2024)
Left-sided colorectal cancer (LSCC) and right-sided colorectal cancer (RSCC) belong to colorectal cancer happening at different positions, which exhibit different pathogenesis. MicroRNA (miRNA)s are widely known regulators in diverse carcinomas. This research aims to identify a differentially expressed miRNA that simultaneously regulates genes associated with LSCC and RSCC and reveal their regulatory relation in cell migration and invasion. Bioinformatics analyses were conducted to uncover the dysregulated functional genes in LSCC/RSCC and obtain their common targeted miRNAs. The expression pattern of miR-27a-3p, TCF7L2, and TGFBR2 in cancerous and adjacent tissues from LSCC/RSCC patients was assessed through qRT-PCR, followed by Pearson’s correlation coefficients analysis. The interaction of miR-27a-3p with TCF7L2 or TGFBR2 was thereafter confirmed through luciferase reporter assay. TCF7L2 and TGFBR2 protein levels were assessed by western blotting after overexpressing level of miR-27a-3p. Cell migration and invasion were routinely examined by wound healing and transwell experiments, respectively. TCF7L2 and TGFBR2 were respectively identified and verified to be lowly expressed in LSCC and RSCC, both of them were predicted and confirmed as targets of miR-27a-3p. MiR-27a-3p elevation exacerbated migration and invasion of both LSCC and RSCC cells. The impacts of miR-27a-3p on migration and invasion could be blocked by overexpressing TCF7L2 in LSCC cells and also reversed by up-regulating TGFBR2 in RSCC cells. In general, miR-27a-3p accelerated the migration and invasion capabilities of LSCC and RSCC cells through negatively regulating TCF7L2 and TGFBR2, respectively, which might be an effective molecular target for the treatment of LSCC/RSCC.